Fluorine-containing polyurethane resin as well as preparation method and application thereof

By preparing fluorine-containing polyurethane resins, the environmental protection and performance deficiencies of traditional polyurethane coatings have been resolved, and high-performance coating materials have been achieved that are self-cleaning, chemically resistant, and adaptable to a wide temperature range, making them suitable for protective coatings and adhesives.

CN120699216AActive Publication Date: 2025-09-26QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511165751.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-06-26
Filing Date
2025-08-20
Publication Date
2025-09-26
Estimated Expiration
2045-08-20

AI Technical Summary

Technical Problem

Traditional polyurethane coatings have problems such as poor environmental friendliness, poor construction performance, insufficient chemical corrosion resistance, poor weather resistance, decreased mechanical properties and weak interface bonding, making it difficult to meet high-end protection needs.

Method used

Fluoropolyurethane resin is prepared using hydrogenated fluorinated polyols and isocyanates. Through solvent-free design, fluorine element modification and hydrogenation treatment, combined with polythiol cross-linking and aliphatic isocyanate, a reinforced coating structure is formed to enhance adhesion, chemical resistance, weather resistance and mechanical strength, and improve the bonding force with the substrate through chemical anchoring and physical adsorption.

Benefits of technology

It achieves environmental protection, construction convenience, wide temperature range adaptability, chemical corrosion resistance and high mechanical strength. The coating has self-cleaning properties and excellent interface bonding strength, and is suitable for the fields of protective coatings and adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120699216A_ABST
    Figure CN120699216A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to fluorine-containing polyurethane resin as well as a preparation method and application thereof. The fluorine-containing polyurethane resin prepared by the preparation method disclosed by the invention is prepared from the following components in parts by weight: 40 to 45 parts of hydrogenated fluorine-containing polyol, 20 to 70 parts of polymercaptan, 50 to 70 parts of isocyanate and 0.6 to 1.2 parts of a catalyst, wherein the hydrogenated fluorine-containing polyol is selected from one or more of hydrogenated hexafluorobisphenol A and hydrogenated hexafluorobisphenol A polyether polyol; the molecular weight of the polymercaptan is 250 to 500; the molar ratio of-OH in the hydrogenated fluorine-containing polyol to-SH in the polythiol to-NCO in the isocyanate is 1: (0-3): (0.5-4). Specifically, fluorine-containing polyhydric alcohols and isocyanate substances are used as initial raw materials, and the solvent-free self-cleaning antifouling fluorine-containing polyurethane coating is prepared through polymerization of a specific reactive aid, so that the preparation of the solvent-free self-cleaning antifouling fluorine-containing polyurethane coating is realized. According to the method, super-strong antifouling self-cleaning of the surfaces of various materials is achieved in the extremely severe environment, waste discharge is reduced, and the method is environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and in particular relates to a fluorine-containing polyurethane resin and a preparation method and application thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Traditional polyurethane coatings are difficult to meet high-end protection needs due to environmental, performance and process defects, and existing improvement solutions have significant shortcomings. For example, traditional polyurethane coating materials have the following technical defects: (1) Solvent-based systems contain a large amount of volatile organic compounds (VOCs), which do not meet environmental protection requirements; (2) Existing solvent-free systems have high viscosity and poor construction performance; (3) Insufficient chemical corrosion resistance, especially in harsh environments such as acid, alkali, and salt spray, which are prone to failure; (4) Narrow temperature resistance range (-30℃~120℃); (5) Poor weather resistance, prone to yellowing and powdering; (6) Mechanical properties significantly decrease at extreme temperatures; (7) High surface energy and insufficient anti-fouling performance.

[0004] Existing improved technologies have made many contributions, but there are still obvious shortcomings: (1) Adding solvents improves processability but causes environmental pollution; (2) Conventional fluorination modification sacrifices the flexibility and mechanical properties of the material; (3) The multi-layer coating system has weak interfacial bonding, is prone to delamination and falls off, and the process is complex and costly.

[0005] Therefore, those skilled in the art are in urgent need of exploring a new type of polyurethane resin that is environmentally friendly (solvent-free, low VOCs), high-performance (wide temperature range adaptability, chemical corrosion resistance, high weather resistance), strong interfacial bonding (avoiding delamination failure), and convenient for construction (low viscosity, easy to coat) to overcome the above problems. Summary of the Invention

[0006] In response to the needs of the prior art, the purpose of the present invention is to provide a fluorine-containing polyurethane resin and its preparation method and application. The material provided by the present invention is prepared by polymerization of hydrogenated fluorine-containing polyols and isocyanates as initial raw materials, and realizes the preparation of solvent-free self-cleaning and anti-fouling fluorine-containing polyurethane coatings. The coating preparation method solves environmental protection problems through solvent-free design; optimizes the formula to achieve low viscosity and improve workability; combines fluorine element modification with hydrogenation treatment to synergistically enhance adhesion, chemical resistance, weather resistance and mechanical strength; adopts polythiol crosslinking and aliphatic isocyanates to avoid aromatic ring oxidation problems and expand temperature range adaptability; and strengthens the bonding force between the resin and the substrate through chemical anchoring (-NCO group) and physical adsorption (alicyclic polarity). It has significant advantages and broad application prospects in the fields of protective coatings, adhesives, etc.

[0007] Specifically, the present invention provides the following technical solutions: A first aspect of the present invention provides a fluorine-containing polyurethane resin, which is composed of the following components, in parts by weight: 40-45 parts of a hydrogenated fluorine-containing polyol, 20-70 parts of a polythiol, 50-70 parts of an isocyanate, and 0.6-1.2 parts of a catalyst; wherein the hydrogenated fluorine-containing polyol is selected from one or more of hydrogenated fluorine-containing bisphenol A and hydrogenated fluorine-containing bisphenol A polyether polyol; the molecular weight of the polythiol is 250-500; and the molar ratio of -OH in the hydrogenated fluorine-containing polyol, -SH in the polythiol, and -NCO in the isocyanate is 1:(0-3):(0.5-4).

[0008] Preferably, the fluorine-containing polyurethane resin is composed of the following components in parts by weight: 42-44 parts of hydrogenated fluorine-containing polyol, 40-50 parts of polythiol, 60-68 parts of isocyanate, and 0.8-1.1 parts of catalyst; the molar ratio of -OH in the hydrogenated fluorine-containing polyol, -SH in the polythiol, and -NCO in the isocyanate is 1:0.8-2.5:2-3.5.

[0009] Preferably, the fluorine-containing polyurethane resin is composed of the following components in parts by weight: 43.5 parts of hydrogenated fluorine-containing polyol, 43.4 parts of polythiol, 66.2 parts of isocyanate, and 1 part of catalyst; the molar ratio of -OH in the hydrogenated fluorine-containing polyol, -SH in the polythiol, and -NCO in the isocyanate is 1:2:3.15.

[0010] Preferably, the hydrogenated fluorinated bisphenol A includes hydrogenated hexafluorobisphenol A, and the hydrogenated fluorinated bisphenol A polyether polyol includes hydrogenated hexafluorobisphenol A polyether polyol, with a molecular weight of 600-800.

[0011] Preferably, the isocyanate is selected from one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), and dicyclohexylmethane diisocyanate (HMDI).

[0012] Preferably, the polythiol is selected from one or more of polythiol 504, polythiol 405, trimethylolpropane tris(3-mercaptopropionate) (TMPMP), and pentaerythritol tetrakis(3-mercaptopropionate) (PETMP).

[0013] Preferably, the catalyst is selected from one or more of triethylenediamine, triethylamine, NN-dimethylethanolamine, trimethylbenzylamine, NN-dimethylcyclohexylamine, dibutyltin dilaurate (DBTDL), and succinic acid.

[0014] Preferably, the fluorine-containing polyurethane resin further comprises a chain extender, and the chain extender is selected from one or more of 1,4-butanediol and ethylenediamine.

[0015] The second aspect of the present invention provides a method for preparing the above-mentioned fluorine-containing polyurethane resin, comprising the following steps: S1, heating the mixed and dissolved fluorinated polyol and the catalyst for reaction, then introducing hydrogen into the resulting suspension, and post-treating the product to obtain a hydrogenated fluorinated polyol; S2. Mix hydrogenated fluorinated polyol, polythiol, isocyanate and catalyst, and conduct continuous heating reaction to obtain the product.

[0016] Preferably, in step S1, the mass ratio of the fluorinated polyol to the catalyst is 5-30:0.1, the concentration of the catalyst is 0.3%-0.6%, and the catalyst is selected from one or more of platinum / carbon catalyst, dibutyltin dilaurate, triethylamine, and triethylenediamine.

[0017] Preferably, in step S1, the heating reaction temperature is 100-150° C., the pressure is 5-15 MPa, and the time is 10-15 h.

[0018] Preferably, the post-treatment includes filtration, reduced pressure distillation, recrystallization and drying, wherein the mixed solvent used in the recrystallization is a mixture of ethanol and water in a mass ratio of 3 to 6:1.

[0019] In step S2, the continuous heating reaction is first heated at 75-140° C. for 1-4 h, and then reacted at 75-140° C. for 1-4 h after the hydrogenated fluorinated polyol is dissolved, and then cooled to 30-40° C. to obtain the product.

[0020] The third aspect of the present invention provides a fluorine-containing polyurethane adhesive, comprising the fluorine-containing polyurethane resin described in the first aspect.

[0021] The fourth aspect of the present invention provides a fluorine-containing polyurethane coating, comprising the fluorine-containing polyurethane resin described in the first aspect.

[0022] The fifth aspect of the present invention provides a method for preparing the fluorine-containing polyurethane coating described in the fourth aspect, which specifically comprises coating the fluorine-containing polyurethane resin described in the first aspect on a substrate and curing the substrate to obtain the coating.

[0023] Preferably, the coating thickness is 50-200 μm, and the coating method is selected from one of scraping, spraying, and brushing; the substrate is selected from a hard substrate and / or a soft substrate, the hard substrate includes metal materials such as stainless steel, inorganic non-metallic materials such as glass and ceramics, and polymer materials such as hard plastics; the soft substrate includes leather, synthetic leather sheets, woven fabrics, non-woven fabrics, soft plastics, etc.; the curing method is curing at 80-150°C for 2-7 hours.

[0024] A sixth aspect of the present invention provides an application of the fluorine-containing polyurethane resin described in the first aspect in the field of protective coatings and / or adhesive materials.

[0025] The beneficial effects achieved by one or more of the above technical solutions of the present invention are as follows: (1) The present invention proposes a polyurethane resin containing atoms such as fluorine, oxygen, and nitrogen. The polymer has excellent adhesion, water resistance, organic solvent resistance, graffiti resistance, self-cleaning, and corrosion resistance. The excellent activity and reactivity of fluorine-containing polymers can firmly bond to a variety of materials, including metal, glass, ceramics, etc., by chemical bonding or physical adsorption with the surface of the substrate. When it is applied to the surface of different substrates by spraying or scraping, it has excellent resistance to harsh environments and can achieve self-cleaning function, making it difficult for dirt to adhere. The synergistic effect of fluorine and polar groups in the polymer network further increases the hydrophobicity and excellent chemical resistance of the polyurethane resin, thereby improving the adaptability of the resin in harsh environments.

[0026] (2) The present invention adopts a solvent-free design to avoid environmental pollution caused by solvent volatilization, while reducing the pores and defects inside the resin, enhancing the density and chemical resistance of the coating, and the solvent-free system reduces the viscosity of the resin, improving the construction performance of scraping, spraying, brushing, etc.; the use of hydrogenated fluorinated polyols (such as hydrogenated hexafluorobisphenol A) improves the weather resistance and stability of the coating, and the hydrogenation treatment eliminates the aromatic ring, reduces the surface energy of the coating, and enhances the hydrophobicity (the contact angle can be as high as 94.1°), thereby improving the self-cleaning performance and resistance. The polythiol reacts with isocyanate to form a thiol carbamate bond, which has a higher bond energy than the traditional carbamate bond, significantly improving the hydrolysis resistance, solvent resistance and thermal stability of the coating. The molecular weight of the polythiol is controlled between 250 and 500, which optimizes the cross-linking density and forms a dense network structure, further enhancing the chemical corrosion resistance and mechanical strength of the coating. Aliphatic isocyanates such as HDI and IPDI are preferred to avoid the yellowing and embrittlement problems of aromatic isocyanates at high temperatures, thereby enhancing the weather resistance and stability of the coating.

[0027] (3) Anti-fouling performance: Fluorine atoms (CF bonds) are oriented on the coating surface to form a low surface energy (10-15 mN / m) barrier with a contact angle of up to 94.1°, which significantly improves the self-cleaning performance. Pollutants are difficult to adhere to and are easy to remove (e.g., marks can be easily erased in anti-graffiti tests); Chemical corrosion resistance: The strong electronegativity and chemical inertness of fluorine atoms form a "shielding layer" that effectively resists corrosion from acids, alkalis, salt spray, etc.; at the same time, the thiocarbamate bond (-NHCOS-) generated by polythiol has higher bond energy and better resistance to hydrolysis and solvent corrosion than traditional carbamate bonds; Weather resistance: Fluorine atoms absorb and scatter ultraviolet light, reducing photodegradation; hydrogenation eliminates aromatic rings, preventing oxidation caused by ultraviolet-sensitive groups. At the same time, aliphatic isocyanates (such as HDI and IPDI) avoid the yellowing problem of aromatic isocyanates, ensuring that the coating maintains a stable color over a long period of time. Wide temperature adaptability: Fluorine (CF bond energy 485 kJ / mol) and thiolcarbamate bonds provide high thermal stability. Hydrogenation treatment prevents high-temperature oxidation, and the solvent-free system reduces porosity. The coating maintains >90% mechanical strength within the -30°C to 150°C temperature range. Mechanical strength: Polythiol (molecular weight 250-500) ensures moderate cross-linking density, forming a dense network and improving coating toughness. At the same time, hydrogenation treatment converts rigid aromatic rings into alicyclic structures, achieving both rigidity and flexibility and avoiding brittle cracking (e.g., maintaining high elongation at break at -30°C). Interfacial bonding strength: The unreacted -NCO groups of excess isocyanate form urea / urethane bonds with the substrate (such as -NH2 in leather), enhancing the bonding strength; at the same time, the alicyclic structure of the hydrogenated fluorinated polyol forms hydrogen bonds with the polar groups of the substrate, improving adhesion (high peel strength).

[0028] (4) The present invention controls the molar ratio of -OH in hydrogenated fluorinated polyol, -SH in polythiol and -NCO in isocyanate to be 1:(0~3):(0.5~4). This ratio ensures that the reaction proceeds fully, forms a uniform cross-linked network, avoids the existence of unreacted groups, and thus improves the overall performance of the coating.

[0029] (5) The present invention achieves a comprehensive improvement in the environmental protection, weather resistance, chemical resistance, mechanical strength and construction performance of the coating through hydrogenation of fluorinated polyols, cross-linking of polythiol, solvent-free design and optimization of aliphatic isocyanates, thus solving the defects of traditional polyurethane resins and having significant advantages and broad application prospects in the field of protective coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0031] Figure 1 This is the Fourier transform infrared spectrum of hydrogenated hexafluorobisphenol A in the embodiment of the present invention, with wave numbers between 500 and 4000 cm -1 ; Figure 2 This is the Fourier transform infrared spectrum of hydrogenated hexafluorobisphenol A in the embodiment of the present invention, with wave numbers between 500 and 1600 cm -1 ; Figure 3 Anti-graffiti tests of different embodiments and comparative examples of the present invention, wherein (a) is a picture of Example 1 and Examples 6-7 before wiping, (b) is a picture of Example 1 and Examples 6-7 after wiping, (c) is a picture of Comparative Examples 2-7 before wiping, and (d) is a picture of Comparative Examples 2-7 after wiping; Figure 4 Figures 2 and 3 are the resistance test graphs of different embodiments and comparative examples of the present invention to 0.1 mol / L hydrochloric acid, wherein (a) is the corrosion graph of the coating of Example 1 and Examples 6-7, (b) is the corrosion graph of the coating of Comparative Examples 2-5, and (c) is the corrosion graph of the coating of Comparative Examples 6-7; Figure 5Figures 2 and 3 are the resistance test graphs of different embodiments and comparative examples of the present invention to 0.1 mol / L sodium hydroxide solution, wherein (a) is the corrosion graph of the coating of Example 1 and Examples 6-7, (b) is the corrosion graph of the coating of Comparative Examples 2-5, and (c) is the corrosion graph of the coating of Comparative Examples 6-7; Figure 6 Figures 2 and 3 are the resistance test graphs of different embodiments and comparative examples of the present invention to 0.1 mol / L sodium chloride solution, wherein (a) is the corrosion graph of the coating of Example 1 and Examples 6-7, (b) is the corrosion graph of the coating of Comparative Examples 2-5, and (c) is the corrosion graph of the coating of Comparative Examples 6-7; Figure 7 Figures 2 and 3 are the resistance test graphs of different embodiments and comparative examples of the present invention to 2% wt potassium permanganate solution, wherein (a) is the corrosion graph of the coating of Example 1 and Examples 6-7, (b) is the corrosion graph of the coating of Comparative Examples 2-5, and (c) is the corrosion graph of the coating of Comparative Examples 6-7; Figure 8 The adhesion strength test of different embodiments of the present invention and comparative examples after lap shearing at -20°C for 24 hours; Figure 9 The adhesion strength test of different embodiments of the present invention and comparative examples after lap shear at 90°C for 2.5 hours; Figure 10 These are the macroscopic sample images of the lap shearing and macroscopic fracture surface images of the samples after being pulled apart of the present invention, wherein (a) is the macroscopic sample image of the lap shearing of Example 1 and Examples 6-7, and (b) is the macroscopic fracture surface image of the samples after being pulled apart of Example 1 and Examples 6-7. DETAILED DESCRIPTION

[0032] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.

[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0034] Example 1: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this embodiment, the fluorine-containing polyurethane coating specifically includes the following raw materials in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate, wherein the molar ratio of hydroxyl group in hydrogenated hexafluorobisphenol A: thiol group in polythiol 504: isocyanate group in HDI is 1:2:3.15.

[0035] The specific steps are as follows: (1) 15 parts by weight of hexafluorobisphenol A was dissolved in 200 mL of anhydrous ethanol and heated to 60°C to completely dissolve it. Then, 0.01 parts by weight of platinum / carbon catalyst (5% by mass of catalyst) was added to the reactor for reaction. The reaction temperature was 120°C, the pressure was 10 MPa, and the reaction time was 12 h. The reactor was stirred until a suspension was formed. Then, hydrogen was used to flush the reactor three times to ensure that no oxygen remained. After the reaction was completed, the catalyst was filtered and recovered using a sintered glass funnel while still hot. The solvent was removed by vacuum distillation to obtain a crude product. The product was recrystallized with a mixed solvent (ethanol: water = 8:2, mass ratio). The obtained product was then vacuum dried at 50°C to obtain a white solid, which was hydrogenated hexafluorobisphenol A (4,4-(perfluoropropane-2,2-diyl)bis(cyclohexane-1-ol)). The yield was 88%. The successful formation of the structure of the product can be confirmed from the Fourier transform infrared spectrum (as shown in FIG. Figure 1~Figure 2 ), of which 650~900 cm -1 The absence of sharp and strong peaks in the range 1500-1600 cm -1 The absence of aromatic ring C=C peaks indicates hydrogenation.

[0036] (2) Under nitrogen protection, 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part of dibutyltin dilaurate catalyst were mixed and heated at 100°C with stirring for 2 h. At this time, hydrogenated hexafluorobisphenol A was dissolved in the system, and the system changed from opaque to transparent liquid. The system was heated at 100°C for 3 h, and then cooled to 40°C. The material was a transparent viscous colloidal liquid, which was a fluorine-containing polyurethane resin.

[0037] Example 2: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this embodiment, only the amount of raw materials added to the fluorinated polyurethane coating was changed, and the remaining steps were identical to those of Example 1. Specifically, the following raw materials were included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 50.5 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI was 1:2:2.4.

[0038] Example 3: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this embodiment, only the amount of raw materials added to the fluorinated polyurethane coating was changed, and the remaining steps were identical to those of Example 1. Specifically, the following raw materials were included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 84.1 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI was 1:2:4.

[0039] Example 4: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this embodiment, only the amount of raw materials added to the fluorinated polyurethane coating was changed, and the remaining steps were identical to those of Example 1. Specifically, the following raw materials were used in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 21.7 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI was 1:1:3.15.

[0040] Example 5: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this embodiment, only the amount of raw materials added to the fluorinated polyurethane coating was changed, and the remaining steps were identical to those of Example 1. Specifically, the following raw materials were included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 65.0 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI was 1:3:3.15.

[0041] Example 6: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this example, only the type of isocyanate in the fluorinated polyurethane coating was changed (HDI was replaced with IPDI), and the remaining steps were identical to those in Example 1. Specifically, the following raw materials were prepared in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 87.4 parts by weight of IPDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in IPDI was 1:2:3.15.

[0042] Example 7: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this example, only the type of isocyanate in the fluorinated polyurethane coating was changed (HDI was replaced with HMDI), and the remaining steps were identical to those in Example 1. Specifically, the following raw materials were prepared in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 103.2 parts by weight of HMDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HMDI was 1:2:3.15.

[0043] Examples 8-9: This example provides a fluorine-containing polyurethane resin and a preparation method thereof In this embodiment, only the type of catalyst in the fluorine-containing polyurethane coating was changed, and the remaining steps were completely the same as those in Example 1. Specifically, dibutyltin dilaurate (DBTDL) was replaced with triethylenediamine and triethylamine, respectively.

[0044] Example 10: This embodiment differs from Example 1 in that polythiol 504 is not added in this embodiment, and the remaining ingredients, contents, and preparation method are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate.

[0045] Comparative Example 1: This comparative example differs from Example 1 in that hydrogenated hexafluorobisphenol A is not added, and the remaining ingredients, contents, and preparation method are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 50443.4 parts by weight of polythiol, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate.

[0046] Comparative Example 2: This comparative example differs from Example 1 in that the amount of raw materials added to the fluorinated polyurethane coating is changed, and the remaining steps are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 6.3 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI is 1:2:0.3.

[0047] Comparative Example 3: This comparative example differs from Example 1 in that the amount of raw materials added to the fluorinated polyurethane coating is changed, and the remaining steps are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 125.7 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI is 1:2:5.98.

[0048] Comparative Example 4: This comparative example differs from Example 1 in that the amount of raw materials added to the fluorinated polyurethane coating is changed, and the remaining steps are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 10.8 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI is 1:0.5:3.15.

[0049] Comparative Example 5: This comparative example differs from Example 1 in that the amount of raw materials added to the fluorinated polyurethane coating is changed, and the remaining steps are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 86.7 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI is 1:4:3.15.

[0050] Comparative Example 6: This comparative example differs from Example 1 in that hydrogenated hexafluorobisphenol A is replaced with hydrogenated bisphenol A. The remaining ingredients, contents, and preparation method are identical to those of Example 1. Specifically, the comparative example comprises the following raw materials in parts by weight: 30.1 parts by weight of hydrogenated bisphenol A, 43.4 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated bisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI is 1:2:3.15.

[0051] Comparative Example 7: This comparative example differs from Example 1 in that hydrogenated hexafluorobisphenol A is replaced with hexafluorobisphenol A in this comparative example, and the remaining ingredients, contents, and preparation method are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 42 parts by weight of hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 66.2 parts by weight of HDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hexafluorobisphenol A: thiol groups in polythiol 504: isocyanate groups in HDI is 1:2:3.15.

[0052] Comparative Example 8: This comparative example differs from Example 1 in that only the type of isocyanate in the fluorinated polyurethane coating is changed (HDI is replaced with TDI). The remaining steps are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 68.6 parts by weight of TDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: mercapto groups in polythiol 504: isocyanate groups in TDI is 1:2:3.15.

[0053] Comparative Example 8: This comparative example differs from Example 1 in that only the type of isocyanate in the fluorinated polyurethane coating is changed (HDI is replaced with MDI). The remaining steps are identical to those of Example 1. Specifically, the following raw materials are included in parts by weight: 43.5 parts by weight of hydrogenated hexafluorobisphenol A, 43.4 parts by weight of polythiol 504, 98.5 parts by weight of MDI, and 1 part by weight of dibutyltin dilaurate. The molar ratio of hydroxyl groups in hydrogenated hexafluorobisphenol A: mercapto groups in polythiol 504: isocyanate groups in TDI is 1:2:3.15.

[0054] Test Example 1: This test example tests the performance of coatings prepared from the resins prepared in Examples 1 to 9 and Comparative Examples 1 to 10.

[0055] Experimental process: The resins prepared in Examples 1 to 9 and Comparative Examples 1 to 10 were taken out, and each sample was coated on a substrate for curing at a curing temperature of 120°C and a curing time of 5 hours. Then, a contact angle test was performed (the instrument used was a contact angle meter (HARKE-SPCA)). The results are shown in Tables 1 and 2: Table 1

[0056] Table 2

[0057] Analysis of the data in Tables 1 and 2 shows that the fluorine atoms (CF bonds) in the hydrogenated fluorinated polyols (e.g., hydrogenated hexafluorobisphenol A) used in the embodiments of the present invention have high electronegativity and small atomic radius, and are oriented on the coating surface to form a low surface energy (10-15 mN / m) barrier, significantly improving hydrophobicity (contact angle up to 94.1°). Among them, the contact angle of Example 1 is 94.1°, which is highly hydrophobic; the contact angle of Example 2 is 89.6°, which is lower than that of Example 1 in terms of the isocyanate content. This is because -NCO itself is hydrophobic (low polarity), and the urethane bond generated after the reaction is also correspondingly hydrophobic, and a corresponding decrease in the isocyanate content will also reduce the hydrophobicity of the material; Example 3 has a higher isocyanate content than Example 1, because CO2 generated by the hydrolysis of excess -NCO may form microbubbles inside the material, the surface roughness is reduced after curing, and the microscopic phase separation is destroyed, and the polar group is enriched on the surface, resulting in a decrease in hydrophobicity; Example 6 replaces HDI with IPDI compared to Example 1, and the contact angle is reduced. This may be because the cyclic structure of IPDI may hinder the complete reaction of -SH and -NCO of the fluorinated thiol, resulting in residual unreacted polar -NCO or -SH groups, and the crosslinking density will be uneven, and the hydrophilic area will be more easily exposed. In Examples 8 and 9, the catalyst was replaced compared to Example 1. The catalyst had a minor impact; selecting an appropriate catalyst can shorten the reaction time and promote a more uniform reaction. In Example 10, no polythiol component was added, and compared to Example 1, the surface was not effectively enriched, resulting in a decreased contact angle. The principles of the other comparative examples are similar to those of the examples.

[0058] (2) Anti-fouling performance test (anti-graffiti, self-cleaning): The specific process is as follows: use a marker to write and mark, leave it at room temperature for 6 hours and wipe it with dry toilet paper; The results show that the marking on the coating prepared in Example 1 can be easily wiped off, the marking on the coating prepared in Example 7 leaves a slight trace after wiping, and the marking on the coating prepared in Example 6 wipes off a layer of the coating after wiping. Compared with Examples 6 and 7, the coating prepared in the embodiment of the present invention has the best anti-graffiti effect (such as Figure 3 (a) and (b)).

[0059] The fluorine atoms (CF bonds) in hydrogenated fluorinated polyols (such as hydrogenated hexafluorobisphenol A) are oriented on the coating surface, forming an ultra-low surface energy barrier that significantly reduces the affinity for oily contaminants (such as marker ink). The high contact angle makes it difficult for liquid contaminants to wet the surface, achieving a "lotus effect" (contaminants roll off easily). like Figure 3As shown in (c) and (d), the hydrogenated bisphenol A in Comparative Example 6 (fluorine-free) does not contain fluorine, the surface energy is increased, the anti-graffiti property is significantly reduced (ink is easy to adhere), and the anti-fouling property is deteriorated; the hexafluorobisphenol A in Comparative Example 7 (unhydrogenated) contains lipophilic aromatic rings, which weakens the oleophobic property (increases the risk of ink penetration), has a high surface energy, and is easily adsorbed by pollutants; Comparative Examples 4~5 (imbalanced -SH ratio) lead to abnormal crosslinking density, ink residue or coating damage, and pollutants are easily infiltrated; Comparative Examples 2~3 change the amount of raw materials added in the fluorine-containing polyurethane coating (-NCO ratio is too low or too high), the performance is reduced, and pollutants are easily adsorbed due to insufficient crosslinking or residual unreacted groups; Comparative Examples 8~9 are damaged and peeled off when wiped, and the surface is damaged due to oxidation and degradation of the aromatic structure.

[0060] (3) Chemical corrosion resistance test: The specific test process is as follows: the prepared sample is coated on a steel bar, heated to 120°C on a heating table, cooled to 100°C for about 4 hours, the sample coating is cured in 2.5 hours, and then left to stand at room temperature for 2 hours.

[0061] 2.5 mL of 0.1 mol / L hydrochloric acid, 0.1 mol / L NaOH solution, 0.1 mol / L NaCl solution, and 2% wt potassium permanganate solution were dropped onto the sample coating on the steel bar and observed before and after 8 h.

[0062] Specific phenomenon: 0.1 mol / L hydrochloric acid: Figure 4 As shown in (a), there is no corrosion mark on the coating of Example 1 (HDI), and there are slight corrosion marks on the coating of Example 6 (IPDI) and Example 7 (HMDI); Figure 4 As shown in (b), the coatings of Comparative Examples 2 to 5 were all severely corroded; Figure 4 As shown in (c), there are corrosion marks on the coating of Comparative Example 6 (hydrogenated bisphenol A), and there are slight corrosion marks on the coating of Comparative Example 7 (hexafluorobisphenol A); 0.1 mol / L NaOH solution: Figure 5 As shown in (a), there is no corrosion mark on the coating of Example 1 (HDI), there is slight corrosion mark on the coating of Example 7 (HMDI), and the corrosion of the coating of Example 6 (IPDI) is deeper than that of Example 7; Figure 5 As shown in (b), the coatings of Comparative Examples 2 to 5 were all severely corroded; Figure 5 As shown in (c), there are corrosion marks on the coating of Comparative Example 7 (hexafluorobisphenol A), and there are slight corrosion marks on the coating of Comparative Example 6 (hydrogenated bisphenol A); 0.1 mol / L NaCl solution: Figure 6As shown in (a), there is no corrosion mark on the coating of Example 1 (HDI), there is slight corrosion mark on the coating of Example 7 (HMDI), and the corrosion of the coating of Example 6 (IPDI) is deeper than that of Example 7; Figure 6 As shown in (b), the coatings of Comparative Examples 2 to 5 were all severely corroded; Figure 6 As shown in (c), white marks were corroded on the coating of Comparative Example 7 (hexafluorobisphenol A), and the surface film of the coating of Comparative Example 6 (hydrogenated bisphenol A) was corroded and fell off; 2% wt potassium permanganate solution: Figure 7 As shown in (a), there is no corrosion mark on the coating of Example 1 (HDI), there is slight corrosion mark on the coating of Example 7 (HMDI), and the corrosion of the coating of Example 6 (IPDI) is deeper than that of Example 7; Figure 7 As shown in (b), the coatings of Comparative Examples 2 to 5 were all severely corroded; Figure 7 As shown in (c), there are corrosion marks on the coating of Comparative Example 7 (hexafluorobisphenol A), and there are slight corrosion marks on the coating of Comparative Example 6 (hydrogenated bisphenol A).

[0063] The analysis is as follows: Hydrogenated fluorinated polyols provide a high content of fluorine atoms (CF bonds). Their strong electronegativity and low surface energy (approximately 10-15 mN / m) significantly enhance the coating's hydrophobicity, reducing the penetration of moisture and chemicals, thereby enhancing chemical corrosion resistance. Furthermore, due to the high CF bond energy (approximately 485 kJ / mol) and strong chemical inertness, they can resist corrosion from acids, bases, oxidants, and other agents, reducing the penetration of chemicals. Furthermore, fluorine atoms form a "shielding layer" within the polymer network, lowering the coating's surface energy and inhibiting the adsorption of pollutants and corrosive media (fluorine forms hydrogen bonds with polar groups such as polyols and isocyanates, enhancing the coating's density). For example: The performance of unhydrogenated hexafluorobisphenol A decreases because the aromatic ring is easily oxidized and degraded; while hydrogenation treatment (see infrared spectrum of Example 1) eliminates the aromatic ring, reduces chemical attack points, and thus improves stability.

[0064] Polythiol components contain thiol groups (-SH), which react with isocyanates to form thiocarbamate bonds (-NHCOS-). These bonds are more resistant to hydrolysis and solvent attack than traditional carbamate bonds (-NHCOO-) (higher bond energy and greater chemical stability). Furthermore, polythiol components with a molecular weight of 250-500 can optimize crosslink density, forming a dense network and reducing chemical diffusion pathways. For example, the performance of Comparative Examples 4-5 (with an unbalanced -SH ratio) deteriorated, demonstrating that controlling the polythiol content is essential for chemical resistance. Furthermore, anti-graffiti testing (Example 1) revealed a smooth coating surface and easy removal of contaminants, indirectly demonstrating the dense crosslink network.

[0065] Isocyanates provide -NCO groups, which react with -OH and -SH groups to form a polyurethane network. Aliphatic isocyanates (such as HDI, IPDI, and HMDI) offer superior chemical resistance and yellowing resistance to aromatic isocyanates (such as TDI) because they lack easily oxidized aromatic rings. For example, the performance of Comparative Examples 2 and 3 (where the -NCO ratio is too low or too high) is impaired due to insufficient crosslinking or residual unreacted groups. In Examples 6 and 7, testing different isocyanates, aliphatic long-chain isocyanates (such as HDI and HMDI) performed better.

[0066] The solvent-free design avoids VOC residues, reduces coating porosity and defects (such as pinholes), and prevents chemical medium penetration (background art points out that solvent-based systems are polluting and prone to failure); at the same time, the hydrogenation step eliminates aromatic rings and improves stability; post-treatment (recrystallization, drying) ensures high purity and reduces chemical degradation caused by impurities, and continuous heating reaction promotes uniform cross-linking to form a defect-free coating.

[0067] Therefore, the high inertness of fluorine element + the stable bonding of polythiol + the oxidation resistance of aliphatic isocyanate + the solvent-free dense structure synergistically achieve: 1) Improved hydrophobicity (high contact angle): Reduced adsorption of water / chemical media; 2) Enhanced chemical barrier: Resistant to erosion by H⁺, OH⁻, Cl⁻ plasma; 3) Suitable for acid, alkali, and salt spray environments, with excellent chemical corrosion resistance.

[0068] (4) Weather resistance test: 1) UV-Aging Resistance: The strong electronegativity of fluorine atoms creates a high-bond energy barrier (485 kJ / mol), effectively absorbing and scattering UV light, reducing photodegradation of the polymer chain. Fluorine atoms are oriented on the coating surface, forming a dense hydrophobic layer that reduces water and oxygen penetration, thereby inhibiting photooxidation. For example, Comparative Example 7 (unhydrogenated hexafluorobisphenol A) exhibits significantly poorer weather resistance than Example 1 (hydrogenated fluoride) due to its aromatic rings (which readily absorb UV light and trigger degradation). Furthermore, the hydrogenation reaction (catalytic hydrogenation at 100-150°C) saturates the aromatic rings in hexafluorobisphenol A into alicyclic structures, eliminating UV-sensitive groups and fundamentally improving light-aging resistance. For example, Comparative Example 6 (hydrogenated bisphenol A without fluorine) and Comparative Example 7 (unhydrogenated hexafluorobisphenol A) both exhibit poor weather resistance, demonstrating the synergistic effect of fluorine and hydrogenation.

[0069] 2) Anti-yellowing: The benzene ring structure of aromatic isocyanates (such as TDI / MDI) easily forms a quinone structure under UV irradiation, causing yellowing. Therefore, the aliphatic type in Examples 1, 5-6 performs better.

[0070] 3) Anti-Powdering: Polythiol (-SH) with a molecular weight of 250-500 forms a thiocarbamate bond (-NHCOS-) with isocyanate, which is more resistant to hydrolysis and thermal decomposition (higher bond energy) than traditional carbamate bonds. In Example 1, a strict molar ratio (-OH:-SH:-NCO = 1:2:3.15) was maintained to ensure complete reaction, forming a dense network, reducing moisture / oxygen diffusion paths, and delaying wet-heat aging. For example, Comparative Examples 4-5 (with an unbalanced -SH ratio) and Comparative Examples 2-3 (with an abnormal -NCO ratio) exhibit insufficient crosslinking, resulting in coatings prone to powdering.

[0071] (5) Temperature change resistance test: The specific test process is as follows: the configured sample is coated on a steel bar with a contact area of ​​125 mm 2 , heated at 120℃ on the heating table, cooled to 100℃ for about 4 hours, the sample coating was cured in 2.5 hours, and allowed to stand at room temperature for 2 hours.

[0072] Three parallel samples of the bonded sample steel strips were taken out and placed in a muffle furnace at 90°C for high-temperature testing for 2.5 hours. Another three parallel samples were taken out and placed at -20°C for low-temperature testing for 24 hours. After that, they were taken out and allowed to stand for 6 hours. After that, they were subjected to a tensile test using a KZ-SSBC-500 electronic universal material testing machine. The adhesion strength was obtained by dividing the force generated during the test by the contact area.

[0073] First, the introduction of fluorine improves thermal stability. The high bond energy of the C-F bond resists thermal degradation, while the low surface energy reduces stress caused by temperature fluctuations. Hydrogenation eliminates the aromatic rings, preventing high-temperature oxidation, which is important for thermal stability, as aromatic rings are susceptible to oxidation and embrittlement at high temperatures.

[0074] Thiocarbamate bonds formed by polythiols are more heat-resistant than traditional carbamate bonds due to the higher bond energy of sulfide bonds. Polythiols with a molecular weight of 250-500 optimize crosslink density. This highly crosslinked network inhibits molecular chain motion during temperature fluctuations, reducing deformation and stress accumulation (suppressing molecular chain slippage and volume expansion during temperature fluctuations). The coating prepared in Example 1 has a molar ratio of 1:2:3.15, ensuring sufficient crosslinking and preventing unreacted groups from causing degradation during thermal cycling.

[0075] Aliphatic isocyanates such as HDI or HMDI have no aromatic rings and can avoid yellowing and embrittlement at high temperatures, while the use of aromatic isocyanates (such as TDI) may perform poorly when subjected to temperature fluctuations.

[0076] In addition, solvent-free systems avoid the pores left behind by solvent evaporation, which can become crack initiation points when the temperature changes.

[0077] The data from the comparative examples supports these views. For example, the temperature resistance of Comparative Examples 6 (fluorine-free) and 7 (unhydrogenated) is reduced due to the lack of fluorine protection and the presence of easily oxidized aromatic rings. The imbalance in the ratios in Comparative Examples 2 and 3 leads to insufficient or excessive cross-linking, affecting thermal stability. For example, too little -NCO (Comparative Example 2) may result in insufficient cross-linking, while too much (Comparative Example 3) leaves unreacted groups that are susceptible to hydrolysis or oxidation during thermal cycling.

[0078] Table 3~4 and Figure 8 is the adhesion strength of the examples and comparative examples at -20°C; Table 3

[0079] Table 4

[0080] Tables 5~6 and Figure 9 is the adhesion strength of the examples and comparative examples at 90°C; Table 5

[0081] Table 6

[0082] Adhesion strength directly reflects the ability of a material to bond to its substrate (or other materials) under temperature fluctuations. Temperature fluctuations can lead to differences in thermal expansion coefficients, internal stress accumulation, or chemical bond breakage, all of which are revealed through changes in adhesion strength. Adhesion strength is a direct indicator of temperature-variation resistance, and its changes quantify the material's tolerance to temperature changes.

[0083] The data in the table show that hydrogenated hexafluorobisphenol A provides hydrophobicity and low surface energy, enhancing interfacial compatibility; its absence reduces adhesion between the coating and the substrate. A low -NCO ratio leads to incomplete reaction with -OH / -SH groups, a sparse crosslinking network, reduced cohesive strength, and decreased adhesion. While an excess of -NCO groups may increase crosslinking density, the isocyanate groups may react with ambient water to form urea bonds (increasing brittleness) or make the molecular chain too rigid, reducing toughness and thus decreasing adhesion strength. If the thiol group ratio is insufficient, a reduced ratio slows the crosslinking rate, resulting in incomplete curing and a reduction in flexible segments. This reduced ratio increases the brittleness of the material. Excessive thiol groups may trigger side reactions or lead to localized excessive crosslinking, resulting in stress concentration and thus reduced adhesion strength. IPDI and HMDI are more rigid and have greater steric hindrance. This ring structure reduces reactivity, reduces crosslinking efficiency, and results in weak adhesion. TDI / MDI contain aromatic rings, which are highly rigid and have poor molecular chain flexibility, preventing stress release during thermal cycling. The aromatic rings are susceptible to UV aging, leading to rapid long-term adhesion strength degradation. Due to the lack of fluorine atoms, hydrogenated bisphenol A exhibits reduced hydrophobicity and chemical stability, making the interface susceptible to moisture and heat corrosion. The aromatic rings of hexafluorobisphenol A are highly rigid, resulting in poor compatibility with polythiol / HDI. Furthermore, the aromatic rings are susceptible to oxidative degradation, resulting in poor thermal stability. Consequently, the adhesion strength is lower than that of Example 1.

[0084] (6) Mechanical strength test: The introduction of fluorine is generally believed to reduce the toughness of the material, but the present invention balances this through hydrogenation (eliminating aromatic rings) and polythiol crosslinking. Specifically, polythiol (molecular weight 250-500) forms a thiocarbamate bond (-NHCOS-) with isocyanate through -SH. Its bond energy (≈310 kJ / mol) is higher than that of traditional carbamate bonds (-NHCOO-, ≈280 kJ / mol), significantly improving network stability. For example, in Comparative Examples 4-5 (-SH ratio imbalance): too low -SH (0.5) results in insufficient crosslinking and weak strength; too high -SH (4) results in excessive crosslinking and increased brittleness.

[0085] Hydrogenation (catalytic hydrogenation at 100-150°C) converts the rigid aromatic ring in hexafluorobisphenol A into an alicyclic structure (FTIR confirmed 1500–1600 cm -1 The absence of a C=C peak enhances molecular chain flexibility. The high bond energy of the C-F bond (485 kJ / mol) provides a rigid backbone, synergistically combining with the alicyclic ring to achieve both rigidity and flexibility (high-temperature creep resistance and low-temperature brittle crack resistance). For example, Comparative Example 6 (hydrogenated bisphenol A, fluorine-free) exhibits insufficient rigidity and decreased high-temperature strength. Comparative Example 7 (non-hydrogenated, containing aromatic rings) exhibits high-temperature oxidative embrittlement of the aromatic rings, resulting in reduced elongation at break.

[0086] Aliphatic isocyanates such as HDI and HMDI lack aromatic structures, thus preventing the embrittlement caused by high-temperature oxidation of aromatic isocyanates such as TDI. For example, the long hexamethylene chains of HDI in the examples impart freedom of molecular chain movement, enhancing low-temperature toughness and achieving a strength retention rate exceeding 90% within the temperature range of -30°C to 150°C. In contrast, the TDI-containing coating in the comparative example experienced a 20% drop in tensile strength at high temperatures (>120°C), leading to low-temperature brittle cracking.

[0087] (7) Peel strength test: Specific testing process: The prepared sample was coated onto the surface of two 12 cm long and 2.5 cm wide PVC strips, bonded together, and then hot-pressed on a 120°C heating plate. After 4 hours, the temperature was lowered to 100°C for 2.5 hours, followed by 2 hours of stabilization at room temperature. All sample strips were subjected to peel and tensile testing using a KZ-8SBC-500 electronic universal materials testing machine. The test data are shown in Tables 7 and 8.

[0088] Hydrogenated hexafluorobisphenol A contains hydroxyl groups (-OH) and alicyclic structures, which can form hydrogen bonds or van der Waals forces with polar groups (such as carboxyl groups and amino groups) on the surface of substrates (such as synthetic leather and metals) to enhance physical adsorption; at the same time, fluorine atoms reduce the surface energy of the coating, but the alicyclic structure retains moderate polarity after hydrogenation treatment, balancing the hydrophobicity and wettability of the substrate, avoiding the "difficult bonding" problem of pure fluorine materials; while in Comparative Example 6 (hydrogenated bisphenol A without fluorine), the peel strength decreases (the lack of fluorine causes the hydrophobic layer to weaken the wettability of the substrate); in Comparative Example 7 (unhydrogenated hexafluorobisphenol A), the rigidity of the aromatic ring is too high, the interfacial stress is concentrated, and the bonding force is weak.

[0089] Unreacted -NCO residues in excess isocyanate can form chemical bonds (urea / urethane bonds) with reactive groups in the substrate (such as -NH2 and -OH in leather) during curing, achieving chemical anchoring. Furthermore, the flexible chains of long-chain aliphatic isocyanates such as HDI and HMDI mitigate thermal stress and inhibit interfacial debonding. However, the insufficient -NCO residue in Comparative Example 2 (a molar ratio of 1:2:0.3) leads to insufficient chemical bonding and weak interfacial adhesion. The thermal expansion coefficient of TDI aromatic isocyanates is mismatched with that of the substrate, making interfacial debonding more likely.

[0090] Polythiol forms a high-density crosslink network, enhancing the coating's bulk strength and preventing cohesive failure under interfacial stress (peel strength depends on the coating's cohesive strength and the minimum interfacial force). Furthermore, the thiocarbamate bonds (-NHCOS-) are resistant to hydrolysis, maintaining interfacial integrity in hot and humid environments. Comparative Example 4 (with a low -SH ratio, a molar ratio of 1:0.5:3.15) showed a loose crosslink network and decreased peel strength.

[0091] Table 7

[0092] Table 8

[0093] (8) Bond strength test (including lap shear strength): Specific test process: The configured sample is coated on the steel bar for bonding, with a contact area of ​​125 mm 2 The overlapped sample steel bars were hot pressed on a heating table at 120°C for 4 hours, then cooled to 100°C for 2.5 hours, and then allowed to stand at room temperature for 2 hours. A tensile test was performed using an XWN-20 microcomputer-controlled electronic universal testing machine. The room temperature adhesion strength was obtained by dividing the force generated during the test by the contact area. The test data are shown in Tables 9-10 and Figure 10 shown.

[0094] like Figure 10 As shown, the macroscopic image of the broken sample ( Figure 10 (a) shows that the sample of Example 6 is in a powdered state and has a weaker viscosity than that of Example 1; the sample of Example 7 has pores, while the sample of Example 1 of the present invention has a relatively complete contact surface.

[0095] The hydroxyl group (-OH) and alicyclic structure in hydrogenated hexafluorobisphenol A can form hydrogen bonds or van der Waals forces with polar groups (such as amino groups and carboxyl groups) on the surface of the substrate (such as synthetic leather and leather), thereby enhancing physical adsorption. For example, in Comparative Example 6 (hydrogenated bisphenol A without fluorine), the adhesion is significantly reduced (the lack of fluorine atoms optimizes the surface energy); in Comparative Example 7 (unhydrogenated hexafluorobisphenol A), the rigidity of the residual aromatic ring leads to interfacial stress concentration and weakened bonding force.

[0096] During curing, the unreacted -NCO residue in excess isocyanate forms covalent bonds (urea / urethane bonds) with reactive groups in the substrate (e.g., -NH2 in leather), achieving chemical anchoring. For example, when the -NCO residue in Comparative Example 2 is insufficient, with a molar ratio of 1:2:0.3, chemical bonding is insufficient, resulting in reduced bond strength.

[0097] Polythiol forms a dense three-dimensional network, enhancing the coating's cohesive strength. The thiocarbamate bonds (-NHCOS-) resist hydrolysis in hot and humid environments, maintaining interfacial stability. For example, in Comparative Example 4 (where the -SH ratio is too low), insufficient crosslinking results in a loose coating and reduced adhesion.

[0098] Table 9

[0099] Table 10

[0100] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A fluorine-containing polyurethane resin, characterized in that The invention is composed of the following components in parts by weight: 40-45 parts of hydrogenated fluorine-containing polyol, 20-70 parts of polythiol, 50-70 parts of isocyanate, and 0.6-1.2 parts of catalyst; wherein the hydrogenated fluorine-containing polyol is selected from one or more of hydrogenated hexafluorobisphenol A and hydrogenated hexafluorobisphenol A polyether polyol; the molecular weight of the polythiol is 250-500; and the molar ratio of -OH in the hydrogenated fluorine-containing polyol, -SH in the polythiol, and -NCO in the isocyanate is 1:(0-3):(0.5-4).

2. The fluorine-containing polyurethane resin according to claim 1, wherein The fluorine-containing polyurethane resin is composed of the following components in parts by weight: 42-44 parts of hydrogenated fluorine-containing polyol, 40-50 parts of polythiol, 60-68 parts of isocyanate, and 0.8-1.1 parts of catalyst; the molar ratio of -OH in the hydrogenated fluorine-containing polyol, -SH in the polythiol, and -NCO in the isocyanate is 1:0.8-2.5:2-3.

5.

3. The fluorine-containing polyurethane resin according to claim 2, wherein The fluorine-containing polyurethane resin is composed of the following components in parts by weight: 43.5 parts of hydrogenated fluorine-containing polyol, 43.4 parts of polythiol, 66.2 parts of isocyanate, and 1 part of catalyst; the molar ratio of -OH in the hydrogenated fluorine-containing polyol, -SH in the polythiol, and -NCO in the isocyanate is 1:2:3.

15.

4. The fluorine-containing polyurethane resin according to claim 1, wherein The isocyanate is selected from one or more of isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate; The polythiol is selected from one or more of polythiol 504, polythiol 405, trimethylolpropane tris(3-mercaptopropionate), and pentaerythritol tetrakis(3-mercaptopropionate); The catalyst is selected from one or more of triethylenediamine, triethylamine, NN-dimethylethanolamine, trimethylbenzylamine, NN-dimethylcyclohexylamine, dibutyltin dilaurate, and succinic acid.

5. A method for preparing the fluorine-containing polyurethane resin according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, heating the mixed and dissolved fluorinated polyol and the catalyst for reaction, then introducing hydrogen into the resulting suspension, and post-treating the product to obtain a hydrogenated fluorinated polyol; S2. Mix hydrogenated fluorinated polyol, polythiol, isocyanate and catalyst, and conduct continuous heating reaction to obtain the product.

6. The preparation method according to claim 5, wherein In step S1, the mass ratio of the fluorinated polyol to the catalyst is 5-30:0.1, the concentration of the catalyst is 0.3-0.6%, and the catalyst is selected from one or more of platinum / carbon catalyst, dibutyltin dilaurate, triethylamine, and triethylenediamine; The heating reaction temperature is 100-150°C, the pressure is 5-15 MPa, and the time is 10-15 h; The post-treatment includes filtration, reduced pressure distillation, recrystallization and drying, wherein the mixed solvent used in the recrystallization is ethanol and water mixed in a mass ratio of 3 to 6:1; In step S2, the continuous heating reaction is first heated at 75-140° C. for 1-4 h, and then reacted at 75-140° C. for 1-4 h after the hydrogenated fluorinated polyol is dissolved, and then cooled to 30-40° C. to obtain the product.

7. A fluorine-containing polyurethane adhesive, characterized in that: The invention comprises the fluorine-containing polyurethane resin according to any one of claims 1 to 4.

8. A fluorine-containing polyurethane coating, characterized in that: The invention comprises the fluorine-containing polyurethane resin according to any one of claims 1 to 4.

9. A method for preparing the fluorine-containing polyurethane coating according to claim 8, characterized in that: The fluorine-containing polyurethane resin is coated on the substrate and cured to obtain the product; The coating thickness is 50-200 μm, and the coating method is selected from one of scraping, spraying, and brushing; the substrate is selected from a hard substrate and / or a soft substrate; and the curing method is vacuum curing at 80-150° C. for 2-7 hours.

10. Use of the fluorine-containing polyurethane resin according to any one of claims 1 to 4 in the field of protective coatings and / or adhesive materials.

Citation Information

Patent Citations

  • Active energy ray-curable resin composition and cured article thereof

    CN104937000A

  • Fluorinated polyurethane coating and preparation method of super-hydrophobic coating

    CN110845952A

  • Anti-doodling polyurethane coating, coating and preparation method and application of anti-doodling polyurethane coating

    CN120173491A

  • Fluorine-containing novolac resin, fluorine-containing surfactant, fluorine-containing surfactant composition, and resin composition

    US20100113678A1

  • Active energy ray-curable resin composition and cured article thereof

    WO2014156454A1